Ketimpangan Pembangunan Antar Kabupaten/Kota di Provinsi Riau: Pendekatan Regresi Kuadratik - Muhammad Hidayat; Sitti Rahayu (LPPM - STIE SAKTI ALAM KERINCI, 2018)
This study aims to determine the development of the level of inequality and the relationship of inequality with economic growth or proof of Neo-Classical hypothesis in Riau Province in 2002-2016. This type of research is descriptive quantitative. The use of secondary data from the publication of the Central Bureau of Statistics. The analysis tools used are Williamson Index and Quadratic Regression. The result of the research shows that in the period of 2002-2016 the development gap in Riau Province is very fluctuating. The rate of change from year to year shows the tendency of the Williamson Index to decrease. Quadratic regression results in negative β2 values, so the Neo-Classical Hypothesis applies in Riau Province.